Recent Advances in Zebrafish Researches 2018
DOI: 10.5772/intechopen.74494
|View full text |Cite
|
Sign up to set email alerts
|

Control of Programmed Cell Death During Zebrafish Embryonic Development

Abstract: Programmed cell death (PCD) is a conserved cellular process, which is essential during embryonic development, morphogenesis and tissue homeostasis. PCD participates in the elimination of unwanted or potentially harmful cells, and contributes in this way to the precise shaping of the developing embryo. In this review, the current knowledge related to the role of PCD during zebrafish development is described and an overview is provided about the main actors that induce, control and execute the apoptotic pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Peripheral effects of cacna1aa LOF (2.5 ng + 2.5 ng) were evidenced by changes in morphology of morphants, i.e., slight hyperpigmentation, lack of swim bladder, and shorter body length-phenotypes also observed in other zebrafish models of epilepsy [22,40]. Notably, cacna1aa mRNA in zebrafish embryos is maternally contributed [41,42], possibly accounting for the higher mortality rate at 24 h than 4 h after injection. Saito et al [43] revealed that knockdown of Cacna1a to 28% of baseline Ca v 2.1 induced severe ataxia, while reduction to 14% dramatically shortened the lifespan of mice.…”
Section: Discussionmentioning
confidence: 89%
“…Peripheral effects of cacna1aa LOF (2.5 ng + 2.5 ng) were evidenced by changes in morphology of morphants, i.e., slight hyperpigmentation, lack of swim bladder, and shorter body length-phenotypes also observed in other zebrafish models of epilepsy [22,40]. Notably, cacna1aa mRNA in zebrafish embryos is maternally contributed [41,42], possibly accounting for the higher mortality rate at 24 h than 4 h after injection. Saito et al [43] revealed that knockdown of Cacna1a to 28% of baseline Ca v 2.1 induced severe ataxia, while reduction to 14% dramatically shortened the lifespan of mice.…”
Section: Discussionmentioning
confidence: 89%
“…Apoptosis is a self-destruction complex and a biochemical process of cells in a multicellular organism. A programmed cell death maintains tissue homeostasis, fetal development, and aging [3]. During apoptosis, the surrounding cells and cellular macromolecules are digested into smaller fragments.…”
Section: Introductionmentioning
confidence: 99%
“…The Bcl-2 family of proteins plays a major role in the regulation of apoptosis, a highly conserved programmed cell death process that eliminates unwanted cells, including damaged cells, which is essential during development [ 1 ]. Dysregulation of this process can lead to cancer or degenerative diseases [ 2 , 3 ] and multiple clinical trials aim to inhibit the Bcl-2 family proteins in cancer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that impaired Bcl-x activity is correlated with the onset of major diseases such as Parkinson’s disease (PD) [ 11 , 12 ], amyotrophic lateral sclerosis [ 13 ] spinal cord muscular atrophy [ 14 ], as well as Friedrich ataxia [ 15 ], however the underlying molecular mechanisms remain poorly characterized. Actually, Bcl-xL seems to play critical roles in a large number of nerve cells, including astrocytes [ 13 ], neurons of the cortex [ 16 ], the hippocampus [ 10 ], the midbrain [ 17 ], the visual and the auditory systems [ 18 , 19 ], motoneurons (MN) [ 14 ] and sensory neurons of the dorsal root ganglion [ 1 ]. The bclx gene encodes 5 isoforms, including Bcl-xL, the major isoform in the CNS.…”
Section: Introductionmentioning
confidence: 99%